Modern Afghanistan a history of struggle and survival - Saikal, Amin; Ravan Farhadi, A. G.; Nourzhanov, Kirill (I.B. Tauris, 2004)
Modern Afghanistan: A History of Struggle and Survival is the definitive study of Afghanistan and its troubles. It will be vital reading for all those who are interested in the new world emerging in the Middle East and Central Asia.